2015
DOI: 10.3855/jidc.6698
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptor (TLR) 2 and TLR4 in the livers of mice infected by Clonorchis sinensis

Abstract: Introduction: Clonorchis sinensis is one of the most important foodborne pathogens in humans, and can cause biliary diseases such as gallstones, cholecystitis, cholangitis, and cholangiocarcinoma. Toll-like receptors (TLRs) as sensors are crucial to initiating both innate and adaptive immune defenses against pathogens. However, little is known about the hepatic expression of TLRs of hosts induced by C. sinensis infection. Methodology: In the present study, the expression and distribution of TLR2 and TLR4 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…However, prolonged inflammation through excessive production of inflammatory cytokines and chemokines via TLR-mediated signaling could be detrimental because it may cause host toxicity and tissue damage. In the mouse model of clonorchiasis, the expressions of TLR2 and TLR4 were upregulated during the infestation of C. sinensis , indicating probable participation of TLR2 and TLR4 in the stimulation of innate immune response during C. sinensis infestation (49). The T H 1-based inflammatory consequences instructed by TLRs are not only involved in eliminating pathogenic infections but can also induce fatal pathogenic consequences (50).…”
Section: Pathogenesis and Carcinogenesismentioning
confidence: 99%
“…However, prolonged inflammation through excessive production of inflammatory cytokines and chemokines via TLR-mediated signaling could be detrimental because it may cause host toxicity and tissue damage. In the mouse model of clonorchiasis, the expressions of TLR2 and TLR4 were upregulated during the infestation of C. sinensis , indicating probable participation of TLR2 and TLR4 in the stimulation of innate immune response during C. sinensis infestation (49). The T H 1-based inflammatory consequences instructed by TLRs are not only involved in eliminating pathogenic infections but can also induce fatal pathogenic consequences (50).…”
Section: Pathogenesis and Carcinogenesismentioning
confidence: 99%
“…sinensis were successful to develop mature in this strain mouse and the levels of TLR4 were highly increased on days of 28 post-infection in C . sinensis -infected C3H mice, compared with health normal mice 11 . Based on these observations, to determine whether TLR4 involves in the PABF or not, we developed C .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that TLR4 was highly expressed in the activated HSC cells and myofibroblasts during C . sinensis -caused biliary fibrosis 11 , but the exact role of TLR4 in the pathological process of PABF caused by C . sinensis still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since TLRs recognize pathogen-associated molecular patterns that are expressed on infectious agents, host cells may recognize liver fluke ESPs through differential activation of TLRs, leading to either the development of effective immunity or pathologic progression, such as activation of the innate mucosal inflammation cascade. In the mouse model for clonorchiasis, the expression of TLR2 and 4 mRNA and proteins in infected livers is up-regulated relatively early in infection (day 28 post-infection), indicating that both TLR2 and TLR4 participate in the stimulation of the innate immune response during C. sinensis infection [20]. …”
mentioning
confidence: 99%